Uniformity detector retinal ganglion cells fire complex spikes and receive only light-evoked inhibition - Sivyer, Benjamin (National Academy of Sciences, 2010)
Retinal ganglion cells convey information by increasing their firing in response to an optimal visual stimulus or “trigger feature.” However, one class of ganglion cell responds to changes in the visual scene by decreasing its firing. These cells, termed uniformity detectors in the rabbit retina, are encountered only rarely and the synaptic mechanisms underlying their unusual responses have not been investigated. In this study, patch-clamp recordings of uniformity detectors show that the action potentials underlying the maintained firing arise within “complex spikes.” Both ON and OFF visual stimuli elicit only inhibitory synaptic input, the immediate effect of which is to suppress the maintained firing. However, this inhibition also alters the properties of the “renascent” spiking by increasing the amplitude of the spikes within each burst, suggesting that the effect may increase the efficacy of spike propagation and transmission.